Poetry and apocalypse : theological disclosures of poetic language - Franke, William (Stanford University Press, 2009)
Here, Franke seeks to find the premises for dialogue between cultures, especially religious fundamentalisms and modern Western secularism. He argues that in order to be genuinely open, dialogue needs to accept possibilities such as religious apocalypse in ways that can be best understood through the experience of poetry.